Assessment of statistical probability of the technological transportation process - Baublys, Adolfas (Transport, 2002)
In the course of freight transportation its technological process is influenced by lots of random factors. The classification of random factors in the whole hierarchical structure of the technological transportation process is presented together with the assessment of the dependence of separate random factors. Statistical information on freight and transport flows is renewed and replenished in the course of time. With the growth of information amount the cost of its storage increases as well. Therefore the relevant algorithms for obtaining required statistical assessment with the least statistical information are presented in the article. It is deduced that in the modelling of transport networks and freights as well as the flows of transport means in them, it is analytically proper to describe random factors by the non-parametric assessment. First Published Online: 19 Dec 2011